3D-QSAR studies of 3-(3, 4-dihydroisoquinolin-2(1H)-ylsulfonyl)benzoic acids as AKR1C3 inhibitors: Highlight the importance of molecular docking in conformation generation. Issue 23 (1st December 2016) - Zheng, Xuehua; Wu, Yinuo; Wu, Deyan; Wang, Xinhua; Zhang, Chao; Guo, Xiaolei; Luo, Hai-Bin
Graphical abstract: Abstract: AKR1C3 is a promising drug target for castration-resistant prostate cancer (CRPC). Here, 3D-QSAR analysis were performed on 3-(3, 4-dihydroisoquinolin-2(1 H )-ylsulfonyl)benzoic acids to correlate their chemical structures with their observed AKR1C3 inhibitory activity. Three structural alignment methods employing various conformers were used to scrutinize the effect of conformation selection on the predictive accuracy of QSAR models. Using docked conformation, the best CoMFA and CoMSIA models were developed and validated with a training set of 61 molecules and a test set of 7 molecules. Detailed analysis of contour maps provided helpful structural insights to rational design of AKR1C3 inhibitors with enhanced potency.